Long-term corrosion behaviour of 1060 aluminium in deep-sea environment of South China Sea. (19th May 2021) - Peng, Wenshan; Duan, Tigang; Hou, Jian; Guo, Weimin; Ding, Kangkang; Cheng, Wenhua; Xu, Likun
ABSTRACT: The serial-type deep-sea environmental test device was used to investigate the corrosion behaviour of 1060 aluminium exposed at real sea for 0.5 year and 2 years. Specimens were deployed at a depth of 1200, 2000 and 3000 m, respectively. A three-stage corrosion process was proposed after analysing the corrosion profile and the corrosion products of the specimens. The corrosion regularity was studied by employing the imaging processing technology and grey correlation analysis. The results show that the 1060 aluminium is prone to pitting and crevice corrosion. For the 0.5 year period test, the corrosion rate increases from 0.0114 to 0.0147 mm year −1 when the sea water depth increases from 1200 to 3000 m. For the 2 year period test, the corrosion rate first decreases and then increases when the sea water depth increases from 1200 to 3000 m, and the maximum corrosion rate at 3000 m depth is 0.006 mm year −1 . Oxygen content and conductivity are the most important factors affecting the corrosion rate.